Fire damage on seeds of Calliandra parviflora Benth. (Fabaceae), a facultative seeder in a Brazilian flooding savanna. Issue 3 (14th May 2021) - dos Santos Ferreira, Bruno Henrique; Guerra, Angélica; da Rosa Oliveira, Maxwell; Reis, Letícia Koutchin; Aptroot, André; Ribeiro, Danilo Bandini; Garcia, Letícia Couto
Abstract: Optimal sexual reproduction in relation to fire effects varies in Fabaceae species. Calliandra species have a large investment in reproduction. We investigated the consequences of fire during the fruiting period of Calliandra parviflora Benth., by checking fruit exposure to fire, pre‐dispersal seed predator infestation, and the effect of fruit burning on germination. We conducted this study in a floodable savanna in central Brazil, where we collected burnt and unburnt fruits. We measured the fruit and seed mass, and counted the number of damaged and undamaged seeds and live larvae per fruit. We analyzed the seed germination percentage from burnt and unburnt fruits. The burnt fruits presented greater mass than the unburnt fruits, despite their seed mass being similar. The number of damaged seeds per fruit was only slightly higher in burnt compared to unburnt fruits ( p  = 0.047). The number of larvae on pre‐dispersal seeds per fruit varied from 0 to 4 and did not differ between burnt and unburnt fruits. The germination percentage of unburnt fruit seeds (mean = 22 ± 17%), was significantly higher than that of burnt fruit (mean = 3.0 ± 2.0%, p  < 0.001). Fire during fruiting or pre‐dispersion decreases seed germination from 22 to 3%, but it does not hurt vegetative regeneration or resprout capacity of C. parviflora, which is a facultative seeder. Hence, we suggest that C. parviflora has potential for post‐fire restoration in floodable open grassy savannas, in the ecotone between Cerrado and Pantanal, because this species may sprout quickly after first post‐fire rains. Abstract : Fire during fruiting or pre‐dispersion decreases seed germination from 22 to 3%, but it does not hurt vegetative regeneration or resprout capacity of Calliandra parviflora, which is a facultative seeder. In addition to fire, the sexual C. parviflora reproduction is under another ecological filter, infestation by seed predators larvae. These ecological filters helps to decrease dissemination of C. parviflora, considering its apparent degree of rusticity. These traits enable its potential for post‐fire restoration in floodable open grassy savannas, in the ecotone between Cerrado and Pantanal, where C. parviflora may sprout quickly after first post‐fire rains.